Tinjauan Hukum Terhadap Gugatan Niet Ontvankelijke Verklaard (No) Tentang Sengketa Tanah Menurut Hukum Acara Perdata - Mustika Putri, Najma Kusumawardhani; Hasanah, Nur; Maharani, Putri; Mastutik, Siti (UNIVERSITAS SERAMBI MEKKAH, 2024)
This exploration aims to understand the Niet Ontvankelijke Verklaard (NO) action in demanding land in civil procedural law as well as the legal way that need to be taken if facing NO action. The exploration uses normative styles. In conclusion, there are two rights for parties whose case is declared NO to file a new action or to appeal, without a clear time limit for when a new action can be filed. piecemeal from that, people frequently misinterpret, considering the NO decision as a defeat, indeed though there are still legal remedies that can be taken.